Erythrocyte phospholipid and polyunsaturated fatty acid composition in diabetic retinopathy. - Philippe Koehrer; Sarah Saab; Olivier Berdeaux; Rodica Isaïco; Stéphane Grégoire; Stéphanie Cabaret; Alain M Bron; Catherine P Creuzot-Garcher; Lionel Bretillon; Niyazi Acar (PLoS ONE, 2014)
Long chain polyunsaturated fatty acids (LCPUFAs) including docosahexaenoic acid and arachidonic acid are suspected to play a key role in the pathogenesis of diabetes. LCPUFAs are known to be preferentially concentrated in specific phospholipids termed as plasmalogens. This study was aimed to highlight potential changes in the metabolism of phospholipids, and particularly plasmalogens, and LCPUFAs at various stages of diabetic retinopathy in humans.We performed lipidomic analyses on red blood cell membranes from controls and mainly type 2 diabetes mellitus patients with or without retinopathy. The fatty acid composition of erythrocytes was determined by gas chromatography and the phospholipid structure was determined by liquid chromatography equipped with an electrospray ionisation source and coupled with a tandem mass spectrometer (LC-ESI-MS/MS). A significant decrease in levels of docosahexaenoic acid and arachidonic acid in erythrocytes of diabetic patients with or without retinopathy was observed. The origin of this decrease was a loss of phosphatidyl-ethanolamine phospholipids esterified with these LCPUFAs. In diabetic patients without retinopathy, this change was balanced by an increase in the levels of several phosphatidyl-choline species. No influence of diabetes nor of diabetic retinopathy was observed on the concentrations of plasmalogen-type phospholipids.Diabetes and diabetic retinopathy were associated with a reduction of erythrocyte LCPUFAs in phosphatidyl-ethanolamines. The increase of the amounts of phosphatidyl-choline species in erythrocytes of diabetic patients without diabetic retinopathy might be a compensatory mechanism for the loss of LC-PUFA-rich phosphatidyl-ethanolamines.